All about nutrients - Curlis, Jim; De Robbio, Michael; Video Education Australasia ([Bendigo, Vic] : Video Education Australasia, 2009)
'Are you eating enough of the right foods to keep yourself healthy? Severe health problems can arise if our body doesn't receive the correct amounts of specific nutrients. But where do these nutrients come from? And in what foods are they found? This program explores the nutritional dangers of not eating a balanced and nutritional diet. We discuss the functions of nutrients as well as different types of food and energy sources. We investigate the difference between macro and micro nutrients, the consequences and associated health problems associated with a poor diet, and the importance of eating a variety of food types in moderation' -- container.
DVD format.
Keywords: Nutrition; Health; Nutritive value